2013
DOI: 10.1002/adsc.201300040
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light Photocatalytic Reduction of Sulfonium Salts as a Source of Aryl Radicals

Abstract: International audienceTriarylsulfonium salts are prompted to undergo efficient homolytic reduction by single electron transfer under mild photocatalytic conditions. The liberated aryl radical can then participate in carbon-carbon bond formation processes with allyl sulfones and activated olefins. Triarylsulfonium salts emerge as a valuable and alternative source of aryl radicals for synthesis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
65
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(66 citation statements)
references
References 127 publications
0
65
1
Order By: Relevance
“…Therefore, we carried out model reactions between 1 and 1,1-diarylethenes 10 (Scheme 5). [14] We found that a nitro group, as well as phenol, pyridine, indole, and thiophene moieties, were unaffected by the reaction conditions, and the corresponding products (11 b-11 g) could be obtained in moderate to good yields. In addition, we evaluated substrates with acid-labile functional groups.…”
Section: Resultsmentioning
confidence: 79%
“…Therefore, we carried out model reactions between 1 and 1,1-diarylethenes 10 (Scheme 5). [14] We found that a nitro group, as well as phenol, pyridine, indole, and thiophene moieties, were unaffected by the reaction conditions, and the corresponding products (11 b-11 g) could be obtained in moderate to good yields. In addition, we evaluated substrates with acid-labile functional groups.…”
Section: Resultsmentioning
confidence: 79%
“…sulfonium salts in photoredox transformations remains underdeveloped. [15] We envisioned that through the combination of nickel-catalyzed cross-coupling of benzylsulfonium salts and the decarboxylative photocatalyzed transformation of Boc-protected prolines a novel synthetic approach could be developed for the synthesis of 2-benzylpyrrolidines in a one-step dual photoredox reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed,v arious benzylsulfonium salts and alkenes could be coupled under visible light irradiation. It is worth mentioning that electrochemical, [9] chemical, [10] and photosensitized [11,12] formations of aryl or alkyl radicals from sulfonium salts have been well studied, while its application to organic synthesis has been limited to a-carbonyl or a-cyanosulfoniums, [10,12] triarylsulfoniums, [13] and 1-trifluoromethyldibenzothiophenium (Umemoto reagent). [14] In the presence of 2mol %o ffac-Ir(ppy) 3 as ap hotocatalyst, the reaction of 1-benzyltetrahydrothiophenium bromide (1a) with 1,1-diphenylethylene (2a)w as tested under blue LED irradiation.…”
mentioning
confidence: 99%